Achromobacter Xylosoxidans Infection in a Patient with Acute Leukemia: Characteristics and Options for Antibiotic Therapy for a Rare Highly Virulent Gram-Negative Bacterium - Suvir Singh; Deepinder Kaur (Indian Journal of Medical Specialities)
Gram-negative infections are a common cause of induction mortality in acute leukemia. Multidrug-resistant (MDR) Gram-negative bacilli are common culprits, contributing to over 40% of deaths in some centers in India. A 20-year-old male with B-cell acute lymphoblastic leukemia, after 5 days of initiation on steroids at another hospital, developed rapid onset dyspnea, with signs of bilateral pneumonia and Type 1 respiratory failure. High-resolution computed tomography of the thorax showed bilateral nodular opacities with ground glassing. Galactomannan was negative, and blood culture isolated MDR Achromobacter xylosoxidans. Antibiotic sensitivity by VITEK2 indicated sensitivity only to ciprofloxacin, levofloxacin, and minocycline. Antibiotics were tailored according to sensitivity, but he had a rapidly worsening downhill course with death from respiratory failure within 72 h. This is only the third case of this organism being described in a patient with malignancy from India. MDR organisms should be suspected whenever a patient with acute leukemia has a history of being in contact with another hospital. In such patients who present with signs of sepsis, it may be reasonable to consider a “de-escalation” approach, with addition of carbapenems upfront and stepping down once cultures are available.